ENERGY AUDIT OF AN INDUSTRIAL SITE: A CASE STUDY - Xakimov Temur; Yusupov is the son of Akromjon Yo’ldosh (Лучшие интеллектуальные исследования, 2024)
Abstract: In order to reduce energy consumptions for sustainable and energy-efficient manufacturing, continuous energy audit and process tracking of industrial machines are essential. Compared to other non-residential buildings that have been widely researched, industrial buildings are generally characterized by larger thermal loads, ventilation losses and pollution control requirements. This paper presents the results of a preliminary energy audit carried out on 8 large industrial buildings of a famous car manufacturing holding . Energy demand for heating varied from 6 to just over 74 kWh/m3year among the buildings of the site. The energy audit enabled to build a specific factory energy model which has been used in order to analyze the impact of various energy saving actions on the primary energy consumptions of the site. It has been demonstrated that in this specific case the improvement of the building envelopes and the optimization of the performances of the existing HVAC systems can determine a reduction of gas consumption up to 15% per year with a predicted annual economic saving of the order of 100000 ; the total simple pay-back time of the proposed thermal retrofitting is evaluated to be less than 6 years..